2017
DOI: 10.1111/cea.12945
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk IgA to foods has different epitope specificity than serum IgA—Evidence for entero‐mammary link for food‐specific IgA?

Abstract: These findings support the concept that mother's milk has a distinct antifood antibody repertoire when compared to the antibody repertoire of the peripheral blood. Increased binding of serum epitope-specific IgA to CM in mothers of infants with CMA may reflect inherited systemic immunogenicity of CM proteins in these families, although specific IgA in breast milk was not proportionally up-regulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The B cells that ultimately produce milk sIgA/sIgM originate mainly from the GALT, known as the entero-mammary link, with some proportion originating from other mucosa such as the respiratory system (1,19,20). Evidence supporting this enteromammary link include the finding that mammary gland B cells display an adhesion receptor profile matching that found on GALT B cells, and that milk sIgA exhibits high reactivity for enteric antigens compared to blood (21)(22)(23)(24). In fact, PRM/Alf mice (possessing elongated intestinal tracts) have been shown to exhibit increased gut-derived B cells in the mammary gland and increased milk sIgA concentration compared to wild type mice (25).…”
Section: Discussionmentioning
confidence: 99%
“…The B cells that ultimately produce milk sIgA/sIgM originate mainly from the GALT, known as the entero-mammary link, with some proportion originating from other mucosa such as the respiratory system (1,19,20). Evidence supporting this enteromammary link include the finding that mammary gland B cells display an adhesion receptor profile matching that found on GALT B cells, and that milk sIgA exhibits high reactivity for enteric antigens compared to blood (21)(22)(23)(24). In fact, PRM/Alf mice (possessing elongated intestinal tracts) have been shown to exhibit increased gut-derived B cells in the mammary gland and increased milk sIgA concentration compared to wild type mice (25).…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal IgAs are produced by plasma cells in the gut lamina propria and are transported across epithelial cells by the polymeric immunoglobulin receptor (pIgR) ( 83 ). Human milk IgA is produced by mammary gland B cells that have migrated from the mother's intestine via the “enteromammary link” ( 84 , 85 ), as shown in animal studies ( 86 – 89 ). This is controlled by the mucosal vascular addressin MadCAM-1 or mucosa-associated epithelial chemokine CCL28, which interacts with the gut homing receptor α 4 β 7 integrin ( 90 ) and mucosa-associated CCR10 ( 91 ).…”
Section: Immunoglobulin a (Iga)mentioning
confidence: 99%
“…Consistent with this, in a rabbit model either oral or inhaled RSV resulted in RSV-IgA production in milk, bronchial and enteral secretions, whereas systemic immunization did not ( 92 ). Studies in humans ( 93 ) showed that oral immunization in women resulted in an increase in plasma cells in milk, but not in saliva or serum, ( 85 ). This forms the hypothesis that human milk IgA reflects the antigenic exposure of the mother's gut to dietary proteins as well.…”
Section: Immunoglobulin a (Iga)mentioning
confidence: 99%
“…31 However, recent research in food allergy has been mostly focused on understanding epitope-specific repertoire of IgE and IgG 4 , with only a limited number of studies addressing epitope specificity of IgG 1 , IgA, and IgD. 41,42 We have previously presented a bead-based epitope assay that is highly reliable and sensitive for detecting milk 43,44 and peanut 45…”
Section: Introductionmentioning
confidence: 99%